The Influence of Incentives and Motivation on Employee Performance of PT. Tozy Sentosa Surabaya - Nur Alifah Istiqomah; Elok Damayanti (Quantitative Economics and Management Studies, 2021)
This study aims to determine the influence of incentives and motivation on the performance of employee of PT. Tozy Santosa Surabaya. This research is quantitative research. Population and sample based on questionnaire distribution to the employees of PT. Tozy Sentosa Surabaya was taken 63 respondents. Data collection techniques used interviews, observation and questionnaires. The data analysis used reliability test, validity test, classic assumption test and multiple linear analysis test. The results of the study, incentives and motivations simultaneously and partially significantly influence the employee performance of PT. Tozy Santosa Surabaya with significance value <0.005.